2021
DOI: 10.1053/j.gastro.2021.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Early-Age Onset Colorectal Neoplasia in Average-Risk Individuals Undergoing Screening Colonoscopy: A Systematic Review and Meta-Analysis

Abstract: BACKGROUND & AIMS: Incidence and mortality associated with early-age onset colorectal cancer (EAO-CRC) is increasing, prompting professional society recommendations to lower the screening age in average-risk individuals. The yield of screening individuals younger than 50 years is not known. METHODS: A systematic review of 3 databases from inception through July 2020 was performed in all languages that reported colonoscopy findings in average-risk individuals younger than 50 years. The primary outcomes were EAO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
24
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 71 publications
4
24
1
1
Order By: Relevance
“…Studies with available data for individuals ages 45 to 49 reported nonadvanced adenoma rates ranging from 8.2% to 20.2% and advanced adenoma rates of 1.2% to 12.5%. [42][43][44][45] Kolb et al 46 conducted a systematic review and meta-analysis of screening colonoscopy performed in 51,811 average-risk individuals under age 50 from 17 international studies published from 2002 to 2020, 5 of which were performed in the United States. Among those ages 45 to 49, this systematic review and meta-analysis reported a pooled rate of any colorectal neoplasia of 17.8% (95% CI, ) and advanced colorectal neoplasia of 3.6% (95% CI, 1.9-6.7).…”
Section: Colonoscopy Screeningmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies with available data for individuals ages 45 to 49 reported nonadvanced adenoma rates ranging from 8.2% to 20.2% and advanced adenoma rates of 1.2% to 12.5%. [42][43][44][45] Kolb et al 46 conducted a systematic review and meta-analysis of screening colonoscopy performed in 51,811 average-risk individuals under age 50 from 17 international studies published from 2002 to 2020, 5 of which were performed in the United States. Among those ages 45 to 49, this systematic review and meta-analysis reported a pooled rate of any colorectal neoplasia of 17.8% (95% CI, ) and advanced colorectal neoplasia of 3.6% (95% CI, 1.9-6.7).…”
Section: Colonoscopy Screeningmentioning
confidence: 99%
“…Based on these pooled rates, 28 average-risk individuals ages 45 to 49 need to undergo screening colonoscopy to detect (and remove) 1 advanced polyp. 46 Butterly et al 47 recently reported rates of neoplasia in 45-to 49-year-olds using data from the New Hampshire Colonoscopy Registry. Because many adults younger than 50 years have colonoscopies for diagnostic indications as opposed to screening, they excluded symptoms shown to be associated with a high risk for advanced neoplasia, such as rectal bleeding, to better approximate an average-risk screening population.…”
Section: Colonoscopy Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, there is evidence that sigmoidoscopy is less effective in women than in men and may be ineffective for older women (18,19). At present, there are no data to support a specific screening modality over others for younger individuals, and recent data suggest that there is a substantial proportion of advanced colorectal neoplasia in the proximal colon of average-risk individuals younger than 50 years (3)(4)(5)(6). Thus, until additional data are available regarding the optimal screening modality in younger individuals, we stand behind our recommendation to offer a tiered menu of screening options, as we do for those older than 50 years.…”
mentioning
confidence: 99%
“…Gerade die Adipositas und der Diabetes mellitus Typ 2 sind weitere wichtige Risikofaktoren für die Entstehung von Darmkrebs. Es sollte auch der Hinweis enthalten sein, dass Menschen unter 50 Jahren mit Risikofaktoren ein erhöhtes Darmkrebsrisiko haben 7 8 .…”
unclassified